(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The environment is the natural surrounding where human and other living beings reside. The patterns of inhibition development and its distinctive characteristics is determined by the actions of mankind and their relation with the environment. Still, the overstated subjection, exploiting and consumption of natural resources of the environment by mankind to fulfill his continuous demands caused a serious environmental deterioration.